Beyond Data Human Rights, Ethical and Social Impact Assessment in AI - Mantelero, Alessandro; SpringerLink (Online service) (The Hague : T.M.C. Asser Press : Imprint: T.M.C. Asser Press, 2022)
This open access book focuses on the impact of Artificial Intelligence (AI) on individuals and society from a legal perspective, providing a comprehensive risk-based methodological framework to address it. Building on the limitations of data protection in dealing with the challenges of AI, the author proposes an integrated approach to risk assessment that focuses on human rights and encompasses contextual social and ethical values. The core of the analysis concerns the assessment methodology and the role of experts in steering the design of AI products and services by business and public bodies in the direction of human rights and societal values. Taking into account the ongoing debate on AI regulation, the proposed assessment model also bridges the gap between risk-based provisions and their real-world implementation. The central focus of the book on human rights and societal values in AI and the proposed solutions will make it of interestto legal scholars, AI developers and providers, policy makers and regulators. Alessandro Mantelero is Associate Professor of Private Law and Law & Technology in the Department of Management and Production Engineering at the Politecnico di Torino in Turin, Italy.
Chapter 1. Beyond Data -- Chapter 2. Human Rights Impact Assessment and AI -- Chapter 3. The Social and Ethical Component in AI Systems Design and Management -- Chapter 4. Regulating AI -- Chapter 5. Open Issues and Conclusions -- Index.
Accessibility summary: This PDF eBook is produced by a third-party. We have requested that the file be made accessible and compliant with the European Accessibility Act (EAA). However, we have not been able to fully verify its compliance with recognized accessibility standards (such as PDF/UA or WCAG). For detailed accessibility information, please refer to the original publisher$1 (Bs website. If you require an accessible version of this content, please contact accessibilitysupport@springernature.com. We are committed to improving accessibility and will work with the publisher to meet your needs wherever possible.s
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Information technology -- Law and legislation; Mass media -- Law and legislation; Human rights; Law -- Europe; Artificial intelligence; Private international law; Conflict of laws; International law; Comparative law; IT Law, Media Law, Intellectual Property; Human Rights; European Law; Artificial Intelligence; Private International Law, International and Foreign Law, Comparative Law; Public International Law